The Rise of Cinematic Santri in Post-Authoritarian Indonesia: Figure, Field and the Competing Discourse - Huda, Ahmad Nuril (Studia Islamika, 2023)
This article examines the past decade’s cinematic rise among young pious Muslims (santri) affiliated with Nahdlatul Ulama (NU), Indonesia’s largest traditionalist Muslim group. It focuses on the social actors, the fields of cultural production, and the competing discourse central to this rise. Its main argument frames the santri’s turn to cinema as symbolic of various changes and continuities in multiple sectors of NU society’s life. It then situates the fields and discourses of the santri’s cinematic practices in the broader set of power relations, consisting of different, at times conflicting, identities and interests that come with being pious Muslims in public domains. To the extent that the efficacy of filmmaking practices and technologies has enhanced the rivalrous inclination of Islam in the post-Suharto Indonesian public sphere, the article offers an insight into the relationship between image-making practices and the politics of representation in a Southeast Asian Islam context.